The RNA content of human sperm reflects prior events in spermatogenesis and potential post-fertilization effects. (5th May 2021) - Corral-Vazquez, C; Blanco, J; Aiese Cigliano, R; Sarrate, Z; Rivera-Egea, R; Vidal, F; Garrido, N; Daub, C; Anton, E
Abstract: Transcriptome analyses using high-throughput methodologies allow a deeper understanding of biological functions in different cell types/tissues. The present study provides an RNA-seq profiling of human sperm mRNAs and lncRNAs (messenger and long non-coding RNAs) in a well-characterized population of fertile individuals. Sperm RNA was extracted from twelve ejaculate samples under strict quality controls. Poly(A)-transcripts were sequenced and aligned to the human genome. mRNAs and lncRNAs were classified according to their mean expression values (FPKM: Fragments Per Kilobase of transcript per Million mapped reads) and integrity. Gene Ontology analysis of the Expressed and Highly Expressed mRNAs showed an involvement in diverse reproduction processes, while the Ubiquitously Expressed and Highly Stable mRNAs were mainly involved in spermatogenesis. Transcription factor enrichment analyses revealed that the Highly Expressed and Ubiquitously Expressed sperm mRNAs were primarily regulated by zinc-fingers and spermatogenesis-related proteins. Regarding the Expressed lncRNAs, only one-third of their potential targets corresponded to Expressed mRNAs and were enriched in cell-cycle regulation processes. The remaining two-thirds were absent in sperm and were enriched in embryogenesis-related processes. A significant amount of post-testicular sperm mRNAs and lncRNAs was also detected. Even though our study is solely directed to the poly-A fraction of sperm transcripts, results indicate that both sperm mRNAs and lncRNAs constitute a footprint of previous spermatogenesis events and are configured to affect the first stages of embryo development.